Analisis Determinan Struktur Modal pada Perusahaan Property dan Real Estate - Sihombing, Febie Tania; Kristanti, Farida Titik (Fakultas Ekonomi Universitas Samudra, 2024)
The aim of this research is to determine the influence of asset tangibility, liquidity, non-debt tax shield, business risk, growth and firm size on the capital structure of property and real estate sector companies listed on the Indonesia Stock Exchange in 2014-2021. A dynamic panel data regression model with the Generalized Method of Moment (GMM) estimator is applied in this research. The results show that determinants simultaneously influence capital structure. Asset tangibility, growth and firm size partially have a significant effect on capital structure, while liquidity, non-debt tax shield and business risk partially have no effect on capital structure. Therefore, the formation of an optimal capital structure is expected to take into account tangible assets, growth rate and company size in order to maximize company value.